1997
DOI: 10.1034/j.1399-3054.1997.1010410.x
|View full text |Cite
|
Sign up to set email alerts
|

Senescence mechanisms

Abstract: Senescence in plants is usually viewed as an intemally programmed degeneration leading to death. It is a developmental process that occurs in many different tissues and serves different purposes. Generally, apoptosis refers to programmed death of small numbers of animal cells, and it shows some special features at the cell level. Some senescing plant cells show some symptoms typical of apoptosis, while others do not. This review will focus primarily on leaf senescence with ultimate aim of explaining whole plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
191
0
17

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(211 citation statements)
references
References 26 publications
3
191
0
17
Order By: Relevance
“…We speculate, however, that the slow remobilization of carbon reserves for HN-WW plants may also relate to the delayed senescence. It is generally assumed that cytokinins play a role in retardation of plant senescence (Buchanan-Wollaston 1997; Nooden et al 1997). We observed that the plants at HN contained much higher cytokinin (Z+ZR) levels in leaves than those at NN (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…We speculate, however, that the slow remobilization of carbon reserves for HN-WW plants may also relate to the delayed senescence. It is generally assumed that cytokinins play a role in retardation of plant senescence (Buchanan-Wollaston 1997; Nooden et al 1997). We observed that the plants at HN contained much higher cytokinin (Z+ZR) levels in leaves than those at NN (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Dierent sets of genes, designated senescence-associated genes (SAGs; Hensel et al 1993;Lohman et al 1994) are up-regulated during senescence and encode proteins involved in the breakdown of cellular components, including ribonucleases, polyubiquitin proteases, and cell wall hydrolases. Other gene products are associated with the mobilization of nutrients and minerals, such as fatty acids, nitrogen compounds and phosphate, out of the senescing tissue and into developing parts of the plants (reviewed in Bleecker and Patterson 1997;Buchanan-Vollaston 1997;Had®eld and Bennett 1997;Nam 1997;Noode n et al 1997;Biswal and Biswal 1999;Quirino et al 2000). However, there is a large overlap of gene expression patterns between senescence and stress-, pathogen-and hormoneresponse (Park et al 1998;Weaver et al 1998;Quirino et al 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Leaf senescence is usually correlated with a decrease in cytokinins in the leaves (Buchanan-Wollaston 1997; Nooden et al 1997). Treatment with cytokinins has been shown to delay leaf senescence in many plants (van Staden et al 1988).…”
Section: Introductionmentioning
confidence: 99%